Evaluation of Sustainable Tourism in the Sierra Alta of Sonora, México: Potential and Challenges of an Emerging Destination (Journal of Management & Business, 2025)
The study explores the potential of the northern zone of the Sierra Alta de Sonora (municipalities of Huachinera, Bacerac, and Bavispe) as an emerging sustainable tourism destination. Despite its natural richness and cultural heritage tied to Jesuit missions and the Ópata culture, the region suffers from tourism underdevelopment. Using a hermeneutic approach, the research analyzed the perceptions of local residents, visitors, and authorities through surveys, participant observation, and documentary analysis to understand the social, cultural, and environmental meanings that shape the territory’s identity. Findings reveal that the area’s value lies not in infrastructure, but in its authenticity, tranquility, pristine landscapes, and the community’s deep connection with nature. The current scarcity of formal tourism services—such as registered accommodations, restaurants, and visitor centers—is interpreted not as a deficit, but as an opportunity to intentionally develop a community-based sustainable tourism model that avoids the pitfalls of mass tourism. Residents prioritize harmony with their environment, necessitating a development path aligned with sustainability, local governance, and the conservation of both cultural and ecological heritage. The study proposes community-based rural tourism routes where visitors engage in activities such as planting, small-scale livestock raising, traditional crafts, and local cuisine, thereby generating income without compromising local identity. In Bavispe, pilot initiatives have already increased household incomes by 30 %. The research concludes that the success of tourism in the Sierra Alta hinges on participatory planning, capacity building, careful regulation of visitor numbers, and the promotion of authentic experiences—positioning the region as a national benchmark for responsible, community-driven, and sustainable tourism.
Keywords: Sierra Alta de Sonora; sustainable tourism; community-based tourism; endogenous development; cultural heritage; local governance; tourism infrastructure; sustainability